Missions, Matrices, and University Management: Reply - Hamelman, Paul W. (Academy of Management Journal, 1971)
The article presents the reply of Professor Paul W. Hamelman to a critique of his article ?Missions, Matrices, and University Management.? Hamelman suggests that certain objections brought up in the criticism of his article can be resolved by determining at which level system analyses are applied within the educational hierarchy. Simulation methods used to represent processes in university management are also discussed.